Insights into determinants of health-seeking behavior: a cross-sectional investigation in the Iraqi context - Mohammed Mkhailef Hawi Al-tameemi; Kaveh Bahmanpour; Amjad Mohamadi-Bolbanabad; Yousef Moradi; Ghobad Moradi (Frontiers Media S.A., 2024)
BackgroundHealth-seeking behavior (HSB) is a choice taken by an individual to maintain, achieve, or restore good health and prevent diseases. The purpose of this study is to examine the determinants of HSB among the Iraqi population.MethodsThis cross-sectional study in the Rusafa and Karkh districts of Baghdad investigated determinants of HSB from 2022 to 2023. With a sample size of 993 participants meeting inclusion criteria, data were collected through a self-reported questionnaire, utilizing four indicators to measure HSB. The study employed various statistical methods especially logistic regression models, facilitated by Stata 17 software.ResultsResults highlights that married individuals consistently have higher odds of having HSB compared to their single counterparts, with an odds ratio (OR) of 2.09 (95% confidence interval: 1.41-3.10). This relationship remains robust even after controlling for other variables. Furthermore, individuals with higher social class exhibit stronger connections to HSB, although the OR is 1.69 (95% CI: 0.47-6.13), indicating a wide confidence interval. Regarding underlying diseases and their duration, the results indicate that chronic diseases are associated with a higher likelihood of HSB, with an OR of 2.05 (95% CI: 1.35-3.11). Additionally, a longer duration of diseases in terms of years is also linked to a stronger association with HSB, with an OR of 2.86 (95% CI: 1.32-6.23).ConclusionIn conclusion, this work provides important insights into HSB. Married people are continuously more likely to engage in HSB than single people, highlighting the importance of customized interventions. Furthermore, persons from higher social classes have stronger ties to HSB, highlighting the importance of socioeconomic considerations. The link between HSB and chronic diseases, combined with longer disease durations, emphasizes the importance of early detection and thorough healthcare management. These findings give critical guidance for healthcare providers, marketers, and politicians developing effective initiatives to promote HSB.